Corporate Social Responsibility (CSR) Dalam Presfektif Hukum Islam - Jejen Suhendar (Fakultas Hukum, Universitas Islam Bandung, 2017)
Issues related to Corporate Social Responsibility (CSR), it is no stranger to the world of law and the company's preformance, when CSR is associated with Islamic law, if in fact Islam has been set in this regard? So that the activities undertaken by these companies is worth worship for businesses. Besides, CSR is an activity undertaken humanitarian nature. Maslahah mursalah While this is a law where there is no dail about the commands and prohibitions.CSR itself is a commitment of the Company to participate in the sustainable economic development to improve the quality of life and environment benefits the Company itself, the local community and society in general. While maslahah mursalah itself has a definition that is a benefit that is not covered by the Personality 'and nor are the arguments sent to work or leave it, whereas if done will bring great good or benefit.